Communism Debated Again: The Muslim Response to the Idea of Revoking the 1966 anti-Communism in Post-Soeharto Indonesia - Ahmad Suhelmi (Studia Islamika, 2006)
This article analyses the responses of the Muslim political elite to President Abdurrahman Wahid's proposal of revoking MPRS Decree No. XXV/1966, which sought to stifle the spread of Communism and the Indonesian Communist Party (PKI). The proposal provoked controversy which divided the Muslim political elite into two groups; those who supported the President's proposal and those who opposed it.DOI: 10.15408/sdi.v13i1.574